Relational Coordination: A Framework for Building Social Capital - Prati, L. Melita (Journal of Organizational Psychology, 2024)
Studies examining employee personal resources have shown many benefits for the individual and his or her organization. Because managers are positioned to engage employees personally, they are the organization’s principal influence to develop subordinate personal resources. This paper develops a model of engaging relational coordination toward developing the personal resources of organizational members. Thus far, little depth of study has been dedicated to the relational coordination concept. Taken from sociology, organizational behavior, politics, and other related fields, the model is constructed to illustrate how managers might utilize the dynamics of relational coordination to facilitate employee resource gains. Specifically, it is suggested that manager activities to engage relational coordination will positively influence member relationships, organizational climate, subordinate attitudes, and interactive practices of organizational members.